Minimization of the Number of Clocks for Timed Scenarios - Saeedloei, Neda; KluŹniak, Feliks (Anais do Simpósio Brasileiro de Métodos Formais (SBMF), 2021)
We present a new optimization algorithm for timed scenarios that achieves the minimal number of clocks when timed scenarios are viewed as timed automata.